Digital Marketing Tools for Preserving Cultural Heritage in the Context of Sustainable Urban Development - Tatyana Oklander; Anastasiia Pandas; Mykhailo Oklander; Oksana Yashkina; Hlib Chaban (Proceedings of the International Conference on Applied Innovations in IT, 2025)
The article is concerned with researching the possibilities of using digital marketing tools in the area of cultural heritage preservation in the context of sustainable urban development. The main focus is on innovative technologies, in particular, on the use of the holographic system “HYPERVSN”, which provides broadcasting of a three-dimensional image with an expressive emotional effect. The methodological basis of the study was general scientific approaches to analysis and systematisation, as well as quantitative methods, including a sociological survey, which made it possible to determine the level of public perception and interest in the use of such technologies in public space. The results indicate the growing openness of consumers to the latest formats of visual communication, as well as the potential of digital media as an effective tool for promoting cultural objects. The research outlines both the advantages, such as innovation, attractiveness, and the ability to create sustainable interest in a city brand, and the risks associated with possible visual overload or inappropriate content of advertising. The originality of the work lies in the integration of a marketing approach to the tasks of cultural heritage protection and in the substantiation of its role in shaping an attractive city image. The practical value lies in the possibility of using the presented findings to develop municipal strategies focused on combining digital technologies, cultural policy and sustainable development.